1995
DOI: 10.1063/1.360764
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced crystallization of isolated amorphous regions in Si, Ge, GaP, and GaAs

Abstract: An energetic electron beam has been used to stimulate crystallization of spatially isolated amorphous regions in Si, Ge, GaP, and GaAs at 30 and 300 K. In the four materials it was found that crystallization was induced even when the energy of the electron beam was less than that required to create point defects in the crystalline structure. The rate of crystallization depended on the material and on the electron energy. In all materials, the rate decreases as the electron energy increases from 50 keV (the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(66 citation statements)
references
References 29 publications
3
57
1
Order By: Relevance
“…More recent TEM observations of isolated zones following ion irradiation have been reported in the compound semiconductors GaAs, GaP, InP (in addition to the elemental semiconductors Si and Ge) [1, 5, 15, 16Ä21]. However, the authors assumed that the observed zones in all the compound and elemental semiconductors investigated were amorphous in nature, based on TEM observations of zones for only GaAs irradiated with heavy ions [22] which appear as dark contrast irregular features in conventional TEM.…”
Section: Introductionmentioning
confidence: 89%
“…More recent TEM observations of isolated zones following ion irradiation have been reported in the compound semiconductors GaAs, GaP, InP (in addition to the elemental semiconductors Si and Ge) [1, 5, 15, 16Ä21]. However, the authors assumed that the observed zones in all the compound and elemental semiconductors investigated were amorphous in nature, based on TEM observations of zones for only GaAs irradiated with heavy ions [22] which appear as dark contrast irregular features in conventional TEM.…”
Section: Introductionmentioning
confidence: 89%
“…The results of radiation zones accumulation under Au (100 keV) irradiation versus uence and ion energy with the use of TEM and RBS/C analysis and a phenomenological model of core creation are presented in [2] and [7], respectively. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using of Rutherford Backscattering Technique (RBS) and Transmission Electron Microscope (TEM) damage structure of irradiated InP SSCS versus the ion uences was studied. Recently, it has been demonstrated that electron irradiation at an energy lower than the threshold energy required to produce direct atomic displacement (point defects) has resulted in zone shrinkage and disappearance in several elemental and compound semiconductors [1,2]. The disappearance rate of thermally and laser-induced recovery of these zones was compared to the electron beam-induced recovery process, it was found that the electron beam-induced recovery was more efˇcient (judging by the disappearance rate versus elapsed time) than theˇrst two processes [3].…”
Section: Introductionmentioning
confidence: 99%
“…One example is beaminduced crystallization and amorphization. This area was actively explored in the 1980s and 1990s, and e-beam crystallization of a number of important semiconductors such as Si [49][50][51][52] and GaAs [52][53][54] has been reported. Similarly, the beam can result in selective removal of material, and when integrated with beam-induced reactions, it can enable fabrication of nanoscale structures, as summarized in recent reviews by Krasheninnikov,55 Gonzales-Martinez, 56 and Jesse.…”
Section: The Third Paradigm: Electron Beamsmentioning
confidence: 99%